Scena prawdy dyskursywnej i postprawdy. „Fakty autentyczne” i fakty medialne we współczesnym teatrze polskim - Dobrowolski, Piotr (Przestrzenie Teorii, 2019)
Theatre practitioners’ statements relating to the notion of truth lead to the category of post-truth. Stage of discursive truth and post-truth article discusses theatre practice of engaging feelings, impressions and emotions to take precedence over interpretations, assessments and descriptions of facts. The article critically approaches using of media discourses in theatre in order to produce the imitation of truth. The author refers to Agnieszka Jakimiak’s and Weronika Szczawińska’s play Wojny, których nie przeżyłam [Wars I have not experienced] and other selected recent Polish plays and performances. The thesis connects the media-shaped image of Polish theatre art institution seen as an area of provocation with an experience of a viewer and an ontological status of an actor. This allows drawing a conclusion that theatre uses the category of truth instrumentally, as one of its repertoire’s tools to provoke emotional reactions in the audience. Theatre performances allow one to explore the world, but also to co-create it. The theatre is a performative and cognitive sieve provoking and shaping experience that affects reality.